(3efHY GdMjGI aj MLjI bhd ddeLJgOjf GdCehGJs - (3fYeI Gddg Hf YHO Gddg Hf eMeO Hf MSjf GdMSjfj GdLRGFQj , J (B1112 (3g` s
(3ChdgG (B:s
(3hHYO HTQM cJGHi GdJgPjH hGdESJHUGQ s
(3BNQgG (B:s
(3Cf GMOgeG hbhY GdJMQja hGdRjGOI hGdfbUGf ai GdeUMa s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI KGfjI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B39 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B110s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B566s
Keywords: (3abg GdePGgH GdCNQis